2005
DOI: 10.1093/aob/mci083
|View full text |Cite
|
Sign up to set email alerts
|

Auxin: Regulation, Action, and Interaction

Abstract: Nearly six decades after the structural elucidation of IAA, many aspects of auxin metabolism, transport and signalling are well established; however, more than a few fundamental questions and innumerable details remain unresolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
1,611
0
63

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,986 publications
(1,752 citation statements)
references
References 344 publications
23
1,611
0
63
Order By: Relevance
“…Our results, including localization, auxin transport as well as genetic and physiological analyses, showed that, although both PIN8 and PIN5 auxin transporters are localized at the ER, they can have antagonistic roles in regulating gametophyte and sporophyte development, cellular auxin homoeostasis and metabolism. PIN5 has been proposed to transport auxin intracellularly from the cytoplasm into the ER, where enzymes involved in IAA metabolism are compartmentalized 6 , thus reducing the auxin availability for the PM-based auxin efflux 24 . It is unclear how PIN8 localized to the same intracellular compartment, namely ER, can act antagonistically but it suggests more complex functional interaction between PIN proteins than anticipated so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, including localization, auxin transport as well as genetic and physiological analyses, showed that, although both PIN8 and PIN5 auxin transporters are localized at the ER, they can have antagonistic roles in regulating gametophyte and sporophyte development, cellular auxin homoeostasis and metabolism. PIN5 has been proposed to transport auxin intracellularly from the cytoplasm into the ER, where enzymes involved in IAA metabolism are compartmentalized 6 , thus reducing the auxin availability for the PM-based auxin efflux 24 . It is unclear how PIN8 localized to the same intracellular compartment, namely ER, can act antagonistically but it suggests more complex functional interaction between PIN proteins than anticipated so far.…”
Section: Discussionmentioning
confidence: 99%
“…T he plant hormone auxin has a crucial role in plant development [1][2][3][4][5][6] . On account of its differential distribution within plant tissues, it acts as a versatile coordinative signal mediating a multitude of processes, including female gametophyte patterning, embryogenesis, organogenesis, meristem activity, growth responses to environmental stimuli and others [7][8][9][10] .…”
mentioning
confidence: 99%
“…IAA is an auxin and some microarrays analyses have demonstrated up-regulation of NIT1 and NIT2 in response to IAN and NaCl treatment (Grsic et al, 1998;Jiang et al, 2007;Woodward and Bartel, 2005). Furthermore, NAC transcription factor also controls salinity stress via the auxin pathway (He et al, 2005;Park et al, 2011).…”
Section: Ataf2 Is Required For Full Induction Of Nit2 In Arabidopsismentioning
confidence: 99%
“…The distribution of auxin depends on both auxin metabolism (biosynthesis, conjugation and degradation) [8][9][10] and cellular auxin transport [11][12][13][14][15] . We identified in silico a novel putative auxin transport facilitator family, called PIN-LIKES (PILS).…”
mentioning
confidence: 99%